2009
DOI: 10.1007/s00011-009-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

An anti-inflammatory lectin from Luetzelburgia auriculata seeds inhibits adhesion and rolling of leukocytes and modulates histamine and PGE2 action in acute inflammation models

Abstract: The results indicate that this lectin is a potent anti-inflammatory molecule. Its effects engage diverse modulatory events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…This shunting is a possible mechanism for the increased ankle swelling seen in the 5-LO -/- mice in the current study. Due to the genetic deletion of 5-LO, increased free AA may be used by COX-2 to produce higher levels of PGE 2 , which is known to induce edema (53). Substrate shunting between these two enzymes has been described previously using specific COX-2 inhibitors (54) or mice deficient in microsomal PGE 2 synthase (55).…”
Section: Discussionmentioning
confidence: 99%
“…This shunting is a possible mechanism for the increased ankle swelling seen in the 5-LO -/- mice in the current study. Due to the genetic deletion of 5-LO, increased free AA may be used by COX-2 to produce higher levels of PGE 2 , which is known to induce edema (53). Substrate shunting between these two enzymes has been described previously using specific COX-2 inhibitors (54) or mice deficient in microsomal PGE 2 synthase (55).…”
Section: Discussionmentioning
confidence: 99%
“…HGA demonstrated the ability to agglutinate human erythrocytes with preference for type A treated with papain. Previous studies have shown the ability of some lectins to reduce the rolling and adhesion of neutrophils on the endothelium, possibly by blocking interactions of adhesion molecules present on neutrophils (L-selectins) and endothelial cells (Eand P-selectins) [26,27,57,58]. Marine lectins are generally identified by their metal ion requirement for their hemagglutination activity.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of marine invertebrate lectins have already been purified and characterized, and considerable attention is focused on its biological recognition role [8][9][10][11][12]. The Table I summarizes the origin, specificity, and biological activity from some lectins [5,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Then, they come as ancestral molecules that show a high degree of conservation during the evolution to superior vertebrates [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were performed in rodents via systemic treatment with lectins that displays binding specificity for glucose–mannose (Assreuy et al ., ; Assreuy et al ., ; Rocha et al ., ; Simoes et al ., ; Pinto et al ., ; Silva et al ., ) and N ‐acetylglucosamine (Alencar et al ., ; Alencar et al ., ; Napimoga et al ., ). However, the anti‐inflammatory effect of galactose‐binding lectins has only been demonstrated for those isolated from the leguminous Luetzelburgia auriculata (Alencar et al ., ).…”
Section: Introductionmentioning
confidence: 99%